ANALISIS KESULITAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI KEMAMPUAN DISPOSISI MATEMATIS SISWA - Dinia, Sofie; Nurhafifah, Astri Yuliani; Mayasari, Mayasari; Patimah, Siti; Hidayat, Wahyu (Journal of Honai Math, 2019)
The purpose of this study was to study and analyze students' problems in problem-solving skills seen from their mathematical disposition level of the students on 12th grade class ofÂ  SMA IT Fithrah Insani. Method of this study is descriptive- qualitative research. From 35 students, there were three students taken as samples, consisting of a student with high disposition mathematical ability (T), a student with medium disposition mathematical ability (S), and a student with low disposition mathematical ability (R). The result of the study shows that there is a difference in the average score of students in each level of the mathematical disposition towards the conclusion of the studentsâ€™ mathematical problem-solving ability test (ANOVA Test-One way). Following up on these differences, researchers identified student achievement and misconceptions on each mathematical problem-solving indicators. The results of the study show that all the student with high and medium disposition mathematical ability could not fulfill the indicators of the ability of mathematical problem solving, such as (1) understand the problem, (2) recheck the answer while all the student with low disposition mathematical ability could not fulfill all indicator of the ability of mathematical problem solving.